PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ESTAFET WRITING UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI BEBAS SISWA KELAS V SD NEGERI 34 PEKANBARU - Novianti, Milla; Kurniaman, Otang; ', Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted because of the lack of students’ ability at the 5th year Elementary School 34 Pekanbaru in writing poetry. From 36 students, there are 13 students who had the strong skill, while the other 23 had a weak skill. This research was aimed to improve the ability to write free poetry of 5th year students of SD Negeri 34 Pekanbaru by using estafet writing strategy. The result of this research showed the improvement in cycle I and II, that is 61,81 improved as much as 74,72 and improved again became 84,17. For the ability in writing free poetry, the students also got the improvement as much as 20,90% in cycle I and got improvement again 36,15% in cycle II. The percentage of teacher’s activity after applying the word square technique at the first meeting was 60% with category ‘enough’. At the second meeting, teacher’s activity became 85% with category ‘very good’. In the cycle II in the second meeting, teacher’s activity became 95% with category ‘very good’. The percentage of students’ activity in the cycle I at the first meeting was 52,5% with category ‘enough’. In the cycle I at the second meeting got the improvement as many as 57,5% with category ‘enough’. In the cycle II at the first meeting, students’ activity got the improvement again became 75% with category ‘very good’, and in the cycle II at the second meeting became 90% with the category ‘very good’. It can be concluded that the application of cooperative strategy estafet writing type can improve the ability in writing a free poetry at the 5th year students of SD N 34 Pekanbaru.Keywords : Estafet Writing, the competence of writing free poetry